Junqueira's basic histology text and atlas - Mescher, Anthony L. (McGraw Hill Education, 2016)
Explains the function of cell and tissue structure in the human body. Updated to reflect the research in the field, and enhanced with more than 1,000 illustrations, this title includes chapters focusing on the cytoplasmic and nuclear compartment of the cell, the four basic tissues that form the organs, and each organ system.